Administrative Division Adjustment and Housing Price Comovement: Evidence from City‐County Mergers in China. Issue 4 (19th July 2022) - Zhang, Sihan; Zhang, Ming‐ang; Sun, Weizeng
Abstract: Interregional housing price comovement is a stylized fact worldwide. This study explores how it is affected by administrative division adjustment. We exploit city‐county mergers in China as a quasi‐natural experiment to construct a difference‐in‐differences strategy for causal identification. Based on monthly housing price data for districts (counties) in China from 2010 to 2019, we find that city‐county mergers significantly improve correlations in housing prices between the merged county and the urban district. This effect is more obvious in cities with a large economic gap between merged counties and urban districts, located in the central and western regions, and with lower administrative hierarchies (non‐provincial‐capital cities). The mechanism test shows that the impact of city‐county mergers on housing price comovement results mainly from integrating housing demand rather than integrating housing supply, like the unified land supply policy that local government implements in the new administrative scope after mergers. The results are helpful in understanding housing price comovement from the view of regional integration and provide clear policy implications for housing market regulation in China.